Review: Detection and Classification of Plants Leaf Diseases - Shahir, Twinkle; Raut, Monali; Khode, Shraddha; Bhagat, Runali; Charde, Vaishnavi (IJRDO -Journal of Computer Science Engineering, 2015)
The aim of this project is todesign, implement and evaluate an imageprocessing software based solution forautomatic detection and classification ofplant leaf disease. We present fast,automatic, cheap and accurate imageprocessing based solution. This solution iscomposed of four main phases. First thedigital images are acquired from the field orenvironment using digital camera. Imagepreprocessing technique noise is removedby filtering technique. Next, in the secondphase, the images are segmented using theK-means clustering technique. In the thirdphase, we calculate the texture features forthe segmented infected objects. Finally, inthe fourth phase the extracted features arepassed through a pre-trained neuralnetwork